Asymptotic properties of the solutions of a class of operator-differential equations. (1994) - Akça, A.; Bainov, D. D.; Dimitrova, M. B.
Abstract : Some asymptotic properties of the nonoscillating solutions of opreator-differential equations of arbitrary order are investigated.